Tr ansatlantic Trade and Investment Partnership: Consigned to Oblivion or Waiting for a Second Chance? - A. О. Mamedova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
The Transatlantic Trade and Investment Partnership (TTIP) between the U.S. and the EU could have become a milestone of the 2010s transforming the current global governance system and the strategic balance of power as well as having a direct impact on the economy and trade. Nevertheless, the negotiations launched in 2013 reached a stalemate and were effectively frozen in January 2017. Although assessments of the new mega bloc’s impact on the U.S. and the EU economies diverged, such a development seems all the more unexpected given that most researchers and politicians advocating the initiative emphasized its geopolitical significance for the West in the face of China’s rise. A question inevitably arises: what can account for the freeze of negotiations? Was it the result of Donald Trump’s election, who was a vocal critic of his predecessor’s legacy during his election campaign? Or are there underlying objective reasons? In order to shed light on the issue it is necessary to analyse the differences that emerged during the fifteen rounds of negotiations as well as to examine the most recent developments in transatlantic trade and economic relations. Trump’s foreign policy sought to advance U.S. national interests in such a way that resulted in weakening multilateral elimination of tariff s for industrial goods and for an agreement on conformity assessment. However, negotiations of the former agreement did not start a year after the Joint Statement had been adopted; there were three meetings of the Executive Working Group focusing on regulatory issues. Apparently, an agreement similar to TTIP in scope is unlikely to be concluded in the near future. It also becomes evident that the parties’ divergent goals and interests at the negotiations rather than subjective factors, such as Donald Trump’s approach, are the main reason for that. Continuing dialogue between the U.S. and the EU on specific issues, e.g. regulation, seems a more viable scenario. Keywords: U.S., EU, trade negotiations, TTIP, transatlantic trade, globalisation, global governance, economic diplomacy, industrial goods, conformity assessment, regulation, tariff and non-tariff barriers.institutions: in 2018 the EU and a number of states became targets of U.S. aluminium and steel tariff s purportedly imposed to protect national security. These unilateral measures turned into leverage ahead of negotiations. In June 2018 the U.S. and the EU issued a Joint Statement: the parties agreed to ‘work together toward zero tariffs, zero non-tariff barriers, and zero subsidies on non-auto industrial goods.’ In April 2019 the Council of the European Union adopted two decisions authorising the opening of negotiations of an agreement with the United States of America on the elimination of tariff s for industrial goods and for an agreement on conformity assessment. However, negotiations of the former agreement did not start a year after the Joint Statement had been adopted; there were three meetings of the Executive Working Group focusing on regulatory issues. Apparently, an agreement similar to TTIP in scope is unlikely to be concluded in the near future. It also becomes evident that the parties’ divergent goals and interests at the negotiations rather than subjective factors, such as Donald Trump’s approach, are the main reason for that. Continuing dialogue between the U.S. and the EU on specific issues, e.g. regulation, seems a more viable scenario.